PENANDA KOHESI GRAMATIKAL DAN LEKSIKAL : KASUS PADA IKLAN CETAK OBAT-OBATAN DAN KOSMETIK - Main Sufanti; Atiqa Sabardila (Kajian Linguistik dan Sastra, 2007)
There are a great number of medicine and cosmetic advertisements in printedmass media. These advertisements are numerous and very productive in term ofexpressing intent so that they emerge interesting language problems to be studied.Lexical and grammatical cohesion markers on those advertisements are written invarious ways. Based on that, the problems of the study are follows: (1) what kind ofcohesion marker developed on medicine and cosmetic advertisements in mass media,(2) how is the form of sentences applied on medicine and cosmetic advertisements.Data collecting method applied in this research is observation method with notingtechnique. The collected data from that technique is then analyzed by distributionalmethod with techniques of substitution, ellipsis, and reading mark.Based on 15 data of discourses in medicine and cosmetic advertisement, it isfound that the lexical and grammatical cohesion markers on those discourse areellipsis, substitution, and repetition. The forms of sentences applied in the discoursesof medicine and cosmetics advertisement are around 1-14 numerous. There arearound 1-14 sentences applied in discourses of medicine and cosmetic advertisement.Based on the analysis of functional structure to sentences used in the discourse,there are 33 functional structures.